Dziecięce kompetencje do przeciwstawiania się w kulturze szkoły polskiej - Monika Wiśniewska-Kin (Problemy Wczesnej Edukacji)
The paper presents the results of an educational research project implemented in the school year 2016/2017 in selected primary schools in urban environment (Łódź). The aim of the study was to diagnose oppositional discursive strategies (initial opposition movements, relationships between partners, reaching agreement), in a group of thirty 8- to 9-year-olds and 9- to 10-year-olds. The research was conducted in a place that provides children with natural play conditions (school common room). The investigator appeared in the role participant as an observer (the researcher came from the examined environment and had the opportunity to “blend into” the events). The material came from participant observation. The observation embraced practical and socio-cognitive activity of the pupils. The results enables recognition of cognitive-social and communicative-interactive competences of the child. In none of the observed opposition episodes physical violence was applied to the interlocutor (only in a few cases children continued to dispute). In the process of reaching agreement in disputable situations, the children focused on agreeing on conflicting behaviours, opinions or views without an adult intermediary (despite the fact that children did not always reach an immediate agreement in the disputed situation).